2015
DOI: 10.1161/jaha.114.001213
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Effectiveness and Cost‐Effectiveness of a Clinical Decision Support System in Managing Hypertension in Resource Constrained Primary Health Care Settings: Results From a Cluster Randomized Trial

Abstract: BackgroundRandomized control trials from the developed world report that clinical decision support systems (DSS) could provide an effective means to improve the management of hypertension (HTN). However, evidence from developing countries in this regard is rather limited, and there is a need to assess the impact of a clinical DSS on managing HTN in primary health care center (PHC) settings.Methods and ResultsWe performed a cluster randomized trial to test the effectiveness and cost‐effectiveness of a clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 38 publications
3
69
0
Order By: Relevance
“…Furthermore, our observations are consistent with other large multifactorial health system interventions (comprising patient registry, evidence‐based guidelines, quality performance metrics, medical assistant, and single pill combination therapy) experiments in the United States such as the Kaiser Permanente Northern California Hypertension program, which resulted in near doubling of hypertension control rates from 43.6% in 2001 to 87.1% in 2011 . In India, a randomized trial of a computer‐based clinical decision support tool for hypertension care at primary care setting has been found to be efficacious and cost‐effective with an estimated reduction of 10.1 mm Hg of SBP in the intervention arm . Another recent community health worker–led trial of cardiovascular risk reduction intervention in rural India and Tibet also demonstrated a reduction of 11.8 mm Hg of SBP in the intervention arm in a setting where people were not accessing follow‐up care from primary care facilities, even after being identified to be at high risk of cardiovascular diseases …”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, our observations are consistent with other large multifactorial health system interventions (comprising patient registry, evidence‐based guidelines, quality performance metrics, medical assistant, and single pill combination therapy) experiments in the United States such as the Kaiser Permanente Northern California Hypertension program, which resulted in near doubling of hypertension control rates from 43.6% in 2001 to 87.1% in 2011 . In India, a randomized trial of a computer‐based clinical decision support tool for hypertension care at primary care setting has been found to be efficacious and cost‐effective with an estimated reduction of 10.1 mm Hg of SBP in the intervention arm . Another recent community health worker–led trial of cardiovascular risk reduction intervention in rural India and Tibet also demonstrated a reduction of 11.8 mm Hg of SBP in the intervention arm in a setting where people were not accessing follow‐up care from primary care facilities, even after being identified to be at high risk of cardiovascular diseases …”
Section: Discussionsupporting
confidence: 83%
“…128 This study concluded that electronic clinical decision support systems are both effective and cost-effective in the management of hypertension in resource-constrained primary care settings. 129 In addition, a multifaceted strategy using mobile technology to assist rural primary healthcare doctors and frontline health workers in CVD risk management has been developed and was implemented in 18 primary health centers and 54 villages in rural Andhra Pradesh involving ≈15 000 adults aged ≥40 years at high CVD event risk. 127 The results of these studies have the potential to inform policy on scalable strategies to improve the efficiency of the health system in managing CVD.…”
Section: Improving Efficiency Of Carementioning
confidence: 99%
“…New nonbattery‐powered devices may soon resolve this problem.Recording the data is critical both for continuing individual patient care as well as to support public health policy making. Paper records are acceptable but, if available, electronic records are more accessible and allow the remote intervention of specialists who can view clinical information and recommend appropriate further testing and therapies . Even low‐income communities can be supported by smart phones, which also can be used to record and transmit data …”
Section: Bp Measurement In Low‐resource Settingsmentioning
confidence: 99%